Microsoft® Visual Web Developer™ 2005 Express Edition: Build a Web Site Now! - Buyens, Jim (Microsoft Press, 2005)
With this lively, eye-opening, and hands-on book, all you need is a computer and the desire to learn how to create Web pages now using Visual Web Developer Express Edition! Featuring a full working edition of the software, this fun and highly visual guide walks you through a complete Web page project from set-up to launch. YouÃ¢??ll get an introduction to the Microsoft Visual StudioÃ#x82;Â® environment and learn how to put the lightweight, easy-to-use tools in Visual Web Developer Express to work right away--building your first, dynamic Web pages with Microsoft ASP.NET 2.0. YouÃ¢??ll get expert tips, coaching, and visual examples at each step of the way, along with pointers to additional learning resources. Visit the catalog page for Microsoft® Visual Web Developer™ 2005 Express Edition: Build a Web Site Now!Visit the errata page for Microsoft® Visual Web Developer™ 2005 Express Edition: Build a Web Site Now!Visit the supplemental content page for Microsoft® Visual Web Developer™ 2005 Express Edition: Build a Web Site Now!